Perilunate dislocation in an asymptomatic SNAC wrist: an uncommon presentation requiring a scaphoidectomy and four corner fusion. (24th November 2014) - Samson, Deepak; Power, Dominic M
Abstract : This report describes a 53-year-old man who presented, following a motocross injury, with a Mayfield stage 1 perilunate dislocation through a pre-existing asymptomatic scaphoid non-union with a degenerative midcarpal joint. A salvage reconstruction with scaphoid excision and four corner midcarpal arthrodesis resulted in a satisfactory outcome. Follow-up at 6 years demonstrated no instability and no further progression of the osteoarthritis.